Outreach of the National Rural Livelihoods Mission through Social and Financial Inclusion: Progress Since its Inception - Gothwal Pooja; Siwach Manoj (Studia Ekonomiczne i Regionalne)
The document is prepared with the objective of examining the outreach of the National Rural Livelihoods Mission through social and financial inclusion of women.